2015
DOI: 10.1080/00918369.2015.1078209
|View full text |Cite
|
Sign up to set email alerts
|

Same-Sex Adoption as a Welfare Alternative? Conservatism, Neoliberal Values, and Support for Adoption by Same-Sex Couples

Abstract: Despite conservatives' long-term opposition to gay and lesbian parenting, scholars theorize that a strong commitment to neoliberalism may influence conservative Americans to become more tolerant of same-sex adoption as a way to relieve the government from subsidizing poor families. Drawing on national survey data (2010 Baylor Religion Survey), we test whether holding neoliberal values is associated with greater support for same-sex adoption in general and across political or religious conservatives. We find no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…The most consistent measure of theological conservatism in studies of public opinion toward homosexuality is adherence to biblical literalism(Perry 2015;Perry and Whitehead 2015), and we follow this precedent in our study. 3 A drawback of using the 2005 BRS is that same-sex marriages gained legal recognition in June 2015, and that attitudes toward homosexuality, same-sex marriage, and adoption have changed since 2005, and thus, it is possible that the association between religion and attitudes toward the various same-sex relationship types may have changed since then.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…The most consistent measure of theological conservatism in studies of public opinion toward homosexuality is adherence to biblical literalism(Perry 2015;Perry and Whitehead 2015), and we follow this precedent in our study. 3 A drawback of using the 2005 BRS is that same-sex marriages gained legal recognition in June 2015, and that attitudes toward homosexuality, same-sex marriage, and adoption have changed since 2005, and thus, it is possible that the association between religion and attitudes toward the various same-sex relationship types may have changed since then.…”
mentioning
confidence: 66%
“…The most consistent measure of theological conservatism in studies of public opinion toward homosexuality is adherence to biblical literalism (Perry ; Perry and Whitehead ), and we follow this precedent in our study.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…In another study, however, Perry () also found that White Americans who were more interested in passing along religious heritage to their children tended to be less supportive of interracial marriage with African Americans, Asians, and Latinos, suggesting that for White Americans, religious identities may be equated with whiteness to some degree. And in related studies, Perry and Whitehead (, ) found that Christian nationalism – a situation in which religious and national identities converge – is a strong predictor of White Americans' opposition to interracial marriage and transracial adoption. These authors propose that the merging of national identity (which is necessarily a reinforcing of social boundaries) with religious identity creates a situation in which national identity is suffused with religious meaning and ethno‐racial boundaries are strongly reinforced.…”
Section: Religion and Interracial Familiesmentioning
confidence: 97%